Analisis Dinamika Legislasi pada Periode Lame Duck dalam Kepemimpinan Politik di Indonesia - Sri Wahyuni; Rosmini Rosmini; Alfian Alfian (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The dynamics of the positions of DPR members cannot be separated from the political activities of lame ducks. However, the lame duck era became problematic because the DPR's legislative activity suddenly increased rapidly towards the end of its term. This increase was accompanied by the controversial passing of a number of bills. This study will examine the urgency of the need for change and the formation of new laws during the lame duck era and the dynamics of the legislative process during the lame duck era of political leadership in Indonesia, using doctrinal research with a legislative and conceptual approach. Based on the research results, it is known that changes and the formation of new laws during the lame duck era lack urgency but will have a negative impact on the quality of legislation and public trust in the government. The dynamics of the legislative process during the lame duck era of political leadership in Indonesia can be reflected in the formation of the fourth revision of the Constitutional Court Bill and the Law on State Ministries. Furthermore, since the first level of deliberation, the process has been closed and rushed without significant public participation. Moreover, Indonesia is currently in a transitional position towards a new government. Therefore, no new regulations should be enacted during this transitional period, as the drafting of the Constitutional Court Bill fails to meet the philosophical, sociological, and legal requirements. Furthermore, the enactment of the State Ministry Law has also sparked controversy, ranging from its substance to its procedural basis.